Alkali–oxygen treatment prior to the mechanical pulping of hardwood enhances enzymatic hydrolysis and carbohydrate recovery through selective lignin modification. Issue 1 (7th November 2018) - Wu, Jie; Chandra, Richard; Saddler, Jack
Abstract : A "one-pot" approach using alkaline-oxygen modified lignin, maximized carbohydrate recovery and increased hydrolysis yields of mechanical pulp more effectively than a pre-hydrolysis approach. Abstract : Aspen chips were impregnated with sodium carbonate (70 °C, overnight) and oxygen (110 °C, 2 hours) prior to pre-steaming (190 °C, 15 min) and mechanical refining. This pretreatment protocol resulted in the removal of 44% of the lignin while retaining 55% of the hemicellulose (which was enriched with carboxylic acid groups (78 mmol kg −1 )) in the water-insoluble fraction. Lignin removal/modification improved fiber swelling and increased cellulose accessibility, resulting in a biomass substrate that could be readily hydrolyzed (80% cellulose hydrolysis, 100% xylan hydrolysis) at an enzyme loading of 20 mg g −1 cellulose. To further enhance the recovery of the hemicellulose component and the susceptibility of the water-insoluble fraction to enzymatic hydrolysis, a pre-hydrolysis (170 °C, 1 hour) step was added prior to alkali–oxygen impregnation. This resulted in a total recovery of 72% of the original hemicellulose from both the solid and liquid fractions. Alternatively, lowering the steaming temperature to 130 °C resulted in the preservation of 72% of the hemicellulose in the water insoluble fraction. Although less lignin was removed at the lower, 130 °C temperature, the resulting lignin contained a greater amount of acid groups (107 mmol of carboxylic acid groups per kg). Substrates containing lignin which were enriched in acid groups showed increased swelling and a decrease in the tendency of the lignin to bind enzymes through hydrophobic interactions. This substantially reduced the negative effects of lignin on enzymatic hydrolysis.